1995
DOI: 10.1108/02686909510079710
|View full text |Cite
|
Sign up to set email alerts
|

Operational auditing education

Abstract: Posits that traditional text‐book‐oriented auditing education is not enough to provide students with the necessary background to become an internal auditor. Proposes that by forming a partnership, in order to enhance internal auditing education, educators and internal auditing professionals can improve a student′s learning. Investigates how this can be done. Suggests that an auditing course provided by the Institute of Internal Auditors (IIA) and the University of Central Florida (UCF) could be the answer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Education is the average number of years of undergraduate and graduate education. Previous studies have recommended the inclusion of internal audit as a separate course in universities (Al-Twaijry, 2006; Cooper, Leung, & Mathews, 1994; Fernandes, Poposky, & Savage, 1995). Certification is the percentage of professional staff members who have the CIA or Certified Public Accountant (CPA) certification.…”
Section: Methodsmentioning
confidence: 99%
“…Education is the average number of years of undergraduate and graduate education. Previous studies have recommended the inclusion of internal audit as a separate course in universities (Al-Twaijry, 2006; Cooper, Leung, & Mathews, 1994; Fernandes, Poposky, & Savage, 1995). Certification is the percentage of professional staff members who have the CIA or Certified Public Accountant (CPA) certification.…”
Section: Methodsmentioning
confidence: 99%
“…These include oral and written communication, teamwork, ethical behavior, critical thinking and problem solving (Bloch, Brewer and Stout, 2012;Jackling and DeLange, 2009). There is evidence that accounting graduates are lacking in oral and written communication skills although research has shown these to be highly important to employability and continued success (Schmidt, Green and Madison, 2009;Fernandes, 1995;Novin and Pearson, 1994. ) In a survey of 422 accounting and financial officers by CFO.com, almost 60 percent said accounting staff lacked the proper communication skills and that this was a barrier to promotion (CFO.com, 2013).…”
Section: Accounting Curricula and Program Designmentioning
confidence: 99%